Social norms as influencers of type 2 diabetes risk-taking behaviours: a qualitative deep-dive diagnosis in two high-burden districts in Uganda - Roy William Mayega; Juliet Kiguli; Francis Xavier Kasujja; Gloria Naggayi; Joseph K B Matovu; Joyce Nabaliisa; Ramadhan Kirunda; Junior Mike Wejuli; Tom Okade; Ninsiima Lesley Rose; Ali Halage (BMJ Open, 2025)
Background Social norms are often implicit informal rules that most people accept and abide by, and can influence how people behave, sometimes based on perceived rewards and/or sanctions. Social norms are propelled by some reference or population groups who exert a considerable amount of influence on behaviour because people value their approval or disapproval. Despite these observations, little research exists on the influence of social norms on diabetes risk-taking behaviours. We explored diet-related social norms and their influence on risk-taking behaviours for type 2 diabetes (T2D).Methods We conducted a multi-method qualitative study guided by the Social Norms Exploration Toolkit participatory tools. A total of 45 participants were interviewed for this study, including (10) T2D patients, (10) caregivers of T2D patients, (10) healthcare providers, (2) village health teams, (4) diabetes-free community members; (4) community influencers like cultural leaders and (5) family members. The study was conducted in eastern Uganda in the districts of Bugiri and Busia. Data were collected on health workers, caregivers, patients and community members using focus group discussions, in-depth interviews and non-participant observation. Data were manually analysed to identify emerging social norms and other information of interest following a thematic framework approach.Results Most participants were aware that frequent consumption of fatty foods and sugary refined foods could increase one’s risk of getting T2D. The study highlights three themes: general awareness of T2D risk factors, common social norms influencing dietary behaviours and behavioural risk factors that are influenced by the social norms. The study highlights significant behavioural and social drivers of T2D, which include consumption of high-fat, high-sugar diets, limited exercise and stress. Gendered and cultural norms strongly influence dietary behaviours, with women preparing unhealthy foods to meet societal expectations, fearing sanctions like divorce or community stigma, while men’s dietary preferences were linked to respect and social status. Norms around staple food preferences and respect linked to weight further perpetuate T2D risk behaviours. Community influencers, family dynamics and cultural traditions reinforce these practices, underscoring the need for gender-transformative, culturally sensitive and community-centred interventions. However, healthcare providers and village health teams are critical for promoting healthier behaviours and reducing T2D prevalence.Conclusion Our deep-dive social norms diagnosis has revealed that even when people know the risk factors for T2D, they will still follow the social norm influence regarding lifestyles. Inclusive strategies that actively engage and reshape norms are therefore vital to reduce the prevalence of T2D.